Monitoring Uninterruptible Power Supply (UPS) Using The Internet Of Things (IoT) - Yosi Apriani; Muhammad Rais Asadullah; Muhammad Hurairoh (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The implementation of a monitoring system on UPS (Uninterruptible Power Supply) which has two energy sources, namely the PLN source and the Battery Source, is very helpful in monitoring the UPS remotely. With this monitoring system, the parameter values ​​on the UPS can be seen (can be monitored) online. The purpose of this study is to design a monitoring system on an IoT (Internet of Things)-based UPS that is useful for viewing the parameter values ​​contained in the UPS directly (real-time) using Sonoff POW R2. This research uses methods starting from the tool design process and the wiring design from the tool manufacturing process and evaluation. The results of the experiment showed that the values ​​on the UPS can be viewed and monitored online and the results showed that the value of the voltage sourced from PLN did not reach 220 V while the value of the voltage sourced from the battery reached 220 V. The value of the current and power sourced from The PLN value shown on the monitoring screen is stable, while the value of current and power sourced from the battery appears to have increased.